IMPROVING STUDENTS' SPEAKING SKILLS BY USING INTERACTIVE METHOD TO ELEVENTH GRADE STUDENTS AT SMA NEGERI 1 DAMPAL SELATAN - Rahmatul Ummu Arifin; Nahdawati Nahdawati (Scolae: Journal of Pedagogy, 2025)
This study aims to improve the speaking skills of eleventh-grade students at SMA Negeri 1 Dampal Selatan through the use of interactive learning methods. The research employed a qualitative approach, with data collected through observations and students’ responses to identify their interests, challenges, and learning needs in English. The findings revealed that 96% of the students believed that English is important for their future. However, 84% of the students still lacked confidence in speaking English, and 96% reported that they rarely used English in daily communication outside the classroom. Nevertheless, the implementation of interactive learning methods was found to enhance students’ confidence in speaking, enrich their vocabulary, improve their fluency in English communication, and encourage more active participation in the learning process. Therefore, interactive learning methods are considered effective in improving students’ speaking skills and creating a more meaningful English learning experience.